2020
DOI: 10.29309/tpmj/2020.27.11.4771
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of VIT D3 and serum ferritin levels in anemic patients in a hospital based study.

Abstract: Objectives: To determine the correlation of Vit D3 levels with serum ferritin in patients with anemia. Study Design: Cross Sectional study. Setting: Department of Pathology, Qazi Hussain Ahmed Medical Complex Nowshera. Period: 5th Jan 2019 to 31st Dec 2020. Material & Methods: Data entered in SPSS 25th version. Descriptive statistics was used for numerical variables. Pearson correlation was used for correlation of Vit D3 with gender. Normality of data was checked by Shapiro wilk test. Mann Whitney U test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
0
1
Order By: Relevance
“…In our study Mean Hemoglobin, Vitamin D and Serum Ferritin were 9.5g/dl, 25.7 and 12ng/ml respectively. Similar findings were reported in a previous study by Hamzullah Khan et al 24 , in 2020, they observed that 118 (61.5%) were iron deficient with serum ferritin less than 15ng/ml and whereas unlike our study Vitamin D3 was insufficient among 7(14.9%) only in ranges between 20.1-29.9ng/ml. Abuaisha M et al 25 , in 2019 reported the prevalence of iron deficiency in 57.5% females at 95%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study Mean Hemoglobin, Vitamin D and Serum Ferritin were 9.5g/dl, 25.7 and 12ng/ml respectively. Similar findings were reported in a previous study by Hamzullah Khan et al 24 , in 2020, they observed that 118 (61.5%) were iron deficient with serum ferritin less than 15ng/ml and whereas unlike our study Vitamin D3 was insufficient among 7(14.9%) only in ranges between 20.1-29.9ng/ml. Abuaisha M et al 25 , in 2019 reported the prevalence of iron deficiency in 57.5% females at 95%.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of our study revealed there is not a significant association between anaemia and vitamin D level and vitamin D and serum Ferritin level among anaemic females of child bearing age showing p value 0.255, dissimilar findings were reported by Hamzullah Khan et al 24 , In 2020 as they found significant association between vitamin D and serum Ferritin with p value 0.02 and they concluded that There is a strong statistically significant association of Vitamin D3 with serum Ferritin in anaemic patients with Hb<11g/dl. In present study a significant association between anaemia and serum ferritin showing p value p=<0.05.…”
Section: Discussioncontrasting
confidence: 81%